Morphometric Analysis of the Foramen Magnum: Insights from Dry Skulls and Imaging Techniques and Clinical Implications - Baisakh, Pratima; Jena, Satyaswarup; Kumari, B. Shanta; Kumar Panda, Dhiren (Journal of Neonatal Surgery, 2025)
Background: The foramen magnum (FM) is a vital structure at the skull base that serves as a conduit for the brainstem and associated vasculature. Their morphometric characteristics provide essential insights into evolutionary adaptations, inter-population variability, and clinical applications. Methods: FM dimensions were analyzed using 50 dry skull specimens and 150 computed tomography (CT) scans. Key measurements were compared between males and females, including the anteroposterior diameter (APD) and transverse diameter (TD). Statistical analyses were performed to determine the significance of sex- and population-based differences. Results: Significant sexual dimorphism was observed, with males generally having larger FM dimensions. In dry skulls, males had a mean APD of 3.54 cm (±0.35) and a TD of 2.94 cm (±0.27), respectively, whereas in dry skulls, males had a mean APD of 3.32 cm (±0.22) and a TD of 2.82 cm (±0.27). CT scan measurements confirmed these findings and demonstrated consistency across methods. Five common FM shapes were identified that showed significant variability across the study population. Conclusion: Understanding FM morphometry is essential for neurosurgical, orthopedic, and forensic applications. Integrating data from dry skulls and CT scans provides a comprehensive understanding of FM variability, aiding surgical planning and enhancing diagnostic accuracy for cranial base conditions.